2019
DOI: 10.1038/s41396-019-0549-y
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated transformation of the gut microbiome and lipidome of bowhead whales provides novel insights into digestion

Abstract: Whale digestion plays an integral role in many ocean ecosystems. By digesting enormous quantities of lipid-rich prey, whales support their energy intensive lifestyle, but also excrete nutrients important to ocean biogeochemical cycles. Nevertheless, whale digestion is poorly understood. Gastrointestinal microorganisms play a significant role in vertebrate digestion, but few studies have examined them in whales. To investigate digestion of lipids, and the potential contribution of microbes to lipid digestion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…Hence, studies of lipid digestion and microbiotas in bowhead whales could provide important information for understanding right whale nutrition. In harvested bowhead whales, lipid digestion and microbial communities were mapped along the gastro intestinal tract (GI, forestomach through colon) by characterizing the lipid compositions (lipidomes) using HPLC-MS/MS and the microbiotas using high-throughput sequencing of the V4 region of the 16S rRNA gene (Miller et al 2020). The lipidomes and microbiotas were tightly correlated as their compositions changed throughout the GI tract, with lipidomes and microbiotas being variable in the small intestine (the area of lipid digestion in mammals).…”
Section: Baleen Whale Microbiomes As Potential Indicators Of Healthmentioning
confidence: 99%
“…Hence, studies of lipid digestion and microbiotas in bowhead whales could provide important information for understanding right whale nutrition. In harvested bowhead whales, lipid digestion and microbial communities were mapped along the gastro intestinal tract (GI, forestomach through colon) by characterizing the lipid compositions (lipidomes) using HPLC-MS/MS and the microbiotas using high-throughput sequencing of the V4 region of the 16S rRNA gene (Miller et al 2020). The lipidomes and microbiotas were tightly correlated as their compositions changed throughout the GI tract, with lipidomes and microbiotas being variable in the small intestine (the area of lipid digestion in mammals).…”
Section: Baleen Whale Microbiomes As Potential Indicators Of Healthmentioning
confidence: 99%
“…In cetaceans, blubber is a specialized form of adipose tissue, densely packed with large spherical adipocytes, which can represent up to 50% of the total body mass in some species at certain life stages (Iverson & Koopman, 2018). Lipid composition of blubber consists mainly of triacylglycerols and reflect both diet and de novo lipogenesis (Bottino, 1978;Gross, 2020;Hansen & Cheah, 1969;Iverson & Koopman, 2018;Kawai et al, 1988;Krahn et al, 2001Krahn et al, , 2004Lafontan & Langin, 2009;Linder et al, 2010;Lockyer et al, 1984;Miller et al, 2020;Ruchonnet et al, 2006;Tilbury et al, 1997;Waugh et al, 2012). Blubber is also an endocrine and complex organ involved in a multitude of physiological and metabolic processes including immune response, energy balance, and lipid metabolism (Deyarmin et al, 2019(Deyarmin et al, , 2020Galligan et al, 2018Galligan et al, , 2020Kershaw et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies investigating lipids in cetaceans only focused on a narrow snapshot of the lipidome, mainly on fatty acids and triacylglycerols (Bagge et al, 2012;Gross, 2020;Hansen & Cheah, 1969;Kawai et al, 1988;Krahn et al, 2004;Ruchonnet et al, 2006;Waugh et al, 2012Waugh et al, , 2014. With the advent of stateof-the-art analytical methods, together with the development of bioinformatics (e.g., Molenaar et al, 2019), the so-called "-omics" disciplines enable more comprehensive systemic profiling to understand the role of lipids in biological systems (Lydic & Goo, 2018;Miller et al, 2020). Thus, the objectives of this study were to document an extended lipidomic fingerprint in killer whales and humpback whales present in northern Norway during wintertime to better understand the determinants of lipid stores and uses in these cetaceans.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the gut microbiota communities of marine mammals have been performed (Nelson et al ., 2013) and research on whales, some dolphin and porpoise species is in the literature (see for instance, Wan et al ., 2018; Kim et al ., 2019; Miller et al ., 2020, Robles-Malagamba et al ., 2020). These studies showed a dominance of members from the phylum Firmicutes and for marine carnivores a high representation of Fusobacteria (Nelson et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%